Advertising and Marketing Strategies: What crafters of new Kenya ought to learn - GM, MURIUKI ROBERT (IJRDO - Journal of Business Management, 2015)
Advertisers and marketers in new Kenya have vast opportunities to be exploited. Since thepromulgation of the new constitution in 2010, devolution to the counties has extended frontiersin advertising and marketing. In the devolved system of government of Kenya today, a lot offinancial and human resources have been directed to the counties where a lot of business can bemade. This paper will look at advertising and marketing strategies the crafters of new Kenyaought to learn so as to maximize on their returns on investment. The paper will explore thechanges that have occurred to marketing over time and those principles and practices that haveendured. There are threats to traditional advertising that need to be embraced. It is importantfor the crafters on new Kenya to be alive to the fact that even with all the advantages ofadvertising, its ubiquitous nature has led to advertising–weary consumers who seize everyavailable opportunity to avoid it. The crafters will also need to learn the new technologies thathave impacted the way advertisement is done separate from traditional advertising. This paperwill look at the new advertising platforms and new techniques that advertisers need to embrace.The paper also makes recommendations on what the crafters of new Kenya need to learn tomitigate the threats that engulf traditional advertising and marketing.